Penerapan Metode Demonstrasi pada Pembelajaran IPA Untuk Meningkatkan Hasil Belajar Siswa Kelas IV SDS 015 Siabu - Musnar Indra Daulay (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2015)
The purpose of research to improve student learning outcomes using Demonstration at fourth grade science lessons Private 015 Siabu Salo District of the Academic Year 2013/2014. This study was conducted in 07 to October 21, 2013 with fourth grade students study subjects who were 30 people. The results of this study were obtained by the procedure of collecting and processing the data as needed in order to improve student learning outcomes, in prasiklus obtained average value of 50.0 with 50% mastery, in cycle 1 increase in learning outcomes obtained an average value of 67.7 with the thoroughness of 80 %, and in the second cycle in the improvement of learning the average value of 78.0 with 90% mastery. Data were obtained from the fourth grade with 30 students. It can be concluded that: "The use of the demonstration method can improve learning outcomes in science lessons sisiwa fourth grade 015 Siabu